2017
DOI: 10.2174/1381612822666161010105242
|View full text |Cite
|
Sign up to set email alerts
|

Salvia miltiorrhiza: A Potential Red Light to the Development of Cardiovascular Diseases

Abstract: Salvia miltiorrhiza Bunge, also known as Danshen in Chinese, has been widely used to treat cardiovascular diseases (CVD) in China and other Asia countries. Here, we summarize literatures of the historical traditional Chinese medicine (TCM) interpretation of the action of Salvia miltiorrhiza, its use in current clinical trials, its main phytochemical constituents and its pharmacological findings by consulting Pubmed, China Knowledge Resource Integrated, China Science and Technology Journal, and the Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
138
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(142 citation statements)
references
References 112 publications
2
138
0
2
Order By: Relevance
“…Danshen is an essential and reliable herb or food for health promotion [17]. Other than polysaccharides and tanshinones, using an HFD rat model, our findings further provide evidence showing that the polyphenolic compounds, ZLB and MLB, represent alternative ingredients of Danshen in the protection against metabolic syndrome.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Danshen is an essential and reliable herb or food for health promotion [17]. Other than polysaccharides and tanshinones, using an HFD rat model, our findings further provide evidence showing that the polyphenolic compounds, ZLB and MLB, represent alternative ingredients of Danshen in the protection against metabolic syndrome.…”
Section: Discussionsupporting
confidence: 61%
“…Increasing evidence shows that many herbal extracts and natural compounds have been implicated in the treatment of metabolic syndrome [6][7][8][9][10][11][12][13]. Particularly, Salvia miltiorrhiza (Danshen), a traditional Chinese medicine used for more than 2000 years, has been frequently prescribed to patients with cardiovascular and metabolic diseases, including diabetes [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The major water‐soluble extract in RSM is phenolic acids (L. Wang, Ma, Liu, et al, ). As shown in Figure a,b as well as Table , several ingredients in RSM aqueous extract were characterized by HPLC‐DAD‐ESI‐MS n , including salvianolic acid H, rosmarinic acid, lithospermic acid, salvianolic acid B, and salvianolic acid L (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that T06 is one of about 60 tanshinone‐related compounds found in S. miltiorrhiza , also known as Danshen in traditional Chinese medicine. Danshen is widely used as an herbal medicine to treat cardiovascular disorders such as atherosclerosis, stroke, and hyperlipidemia, and skeletal diseases such as arthritis and osteoporosis . For example, the herbal extract is a component in more than 30 herbal prescriptions for the treatment of osteoporosis where clinical trials have been reported .…”
Section: Discussionmentioning
confidence: 99%